2020
DOI: 10.1099/mic.0.000995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host-mimicking medium and biofilm growth on the ability of colistin to kill Pseudomonas aeruginosa

Abstract: In vivo biofilms cause recalcitrant infections with extensive and unpredictable antibiotic tolerance. Here, we demonstrate increased tolerance of colistin by Pseudomonas aeruginosa when grown in medium that mimics cystic fibrosis (CF) sputum versus standard medium in in vitro biofilm assays, and drastically increased tolerance when grown in an ex vivo CF model versus the in vitro assay. We used colistin conjugated to the fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
5
17
0
Order By: Relevance
“…I seem destined to not write about papers coming out of Freya Harrisons’ (@friendlymicrobe) lab at the University of Warwick, UK, as her new paper in this month’s issue has been selected as the Editor’s Choice for January. This remarkable achievement follows a previous paper from the same first author Esther Sweeney (@SweeneyEsther) which was published just last month [19]. In her new paper Esther, working with clinicians Matthew Hurley (@MatthewNHurley) and Alan Smyth (@AlanRSmyth) at the University of Nottingham, along with Marwa Hassan (@DrMarwa_Hassan) and Niamh Harrington (@_NiamhEllen) with other colleagues in Nottingham, have made further progress using a porcine lung model they developed previously [20], to now demonstrate that this also functions as a suitable model for studying how Staphylococcus aureus grows during chronic infections of the cystic fibrosis lung [21].…”
Section: Full-textsupporting
confidence: 76%
“…I seem destined to not write about papers coming out of Freya Harrisons’ (@friendlymicrobe) lab at the University of Warwick, UK, as her new paper in this month’s issue has been selected as the Editor’s Choice for January. This remarkable achievement follows a previous paper from the same first author Esther Sweeney (@SweeneyEsther) which was published just last month [19]. In her new paper Esther, working with clinicians Matthew Hurley (@MatthewNHurley) and Alan Smyth (@AlanRSmyth) at the University of Nottingham, along with Marwa Hassan (@DrMarwa_Hassan) and Niamh Harrington (@_NiamhEllen) with other colleagues in Nottingham, have made further progress using a porcine lung model they developed previously [20], to now demonstrate that this also functions as a suitable model for studying how Staphylococcus aureus grows during chronic infections of the cystic fibrosis lung [21].…”
Section: Full-textsupporting
confidence: 76%
“…This can be quantified using standard repeatability calculations after ANOVA 25 ; we have found that there is typically greater variation between CFU in replicate lung samples for S. aureus than for P. aeruginosa. We recommend that, on adoption of the model by a laboratory, repeat calculations are conducted on pilot experiments to optimize experimental techniques and to determine samples sizes to be used in final experiments (an example of this may be found in the data supplement for Sweeney et al 26 ).…”
Section: Representative Resultsmentioning
confidence: 99%
“…These suggested that using depolymerases as a stand-alone treatment might not be sufficient in controlling infections associated with biofilms. Impairing drug diffusion (subdiffusion) within the biofilm matrix is a major contributor to the sub-optimal treatment to biofilm related infections [48]. Improving the antibiotics penetration into the biofilm matrix may hold the key to better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%